2019
DOI: 10.1101/701797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phospholamban and sarcolipin share similar transmembrane zipper motifs that control self-association affinity and oligomer stoichiometry

Abstract: We have characterized the structural determinants of phospholamban (PLB) and sarcolipin (SLN) self-association using site-directed mutagenesis, SDS-PAGE, and fluorescence resonance energy transfer (FRET) microscopy. PLB and SLN are single-pass transmembrane (TM) peptides that are critically involved in regulation of contractility in cardiac and skeletal muscle via reversible inhibition of calcium (Ca) transport by SERCA. PLB and SLN also exhibit ion channel activity in vitro, yet the physiological significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…This interface, combined with the reduced stability of the SLN pentamer, may explain why an SLN monomer was found associated with the M3 site. As stated above, the residues involved are on the opposite face of the SLN transmembrane helix (Leu 8 , Phe 12 , Leu 16 , and Ile 20 ) compared to the residues that stabilize the model of the SLN pentamer (Leu 10 , Ile 14 , Ile 17 , Leu 21 , Leu 24 , and Ser 28 ), and the SLN monomer appears to form a more direct interface with M3 of SERCA than the PLN pentamer. The different interactions between PLN and SLN and the M3 site of SERCA correlate with distinct functional effects on the V max of SERCA.…”
Section: Interaction Between Serca and Slnmentioning
confidence: 88%
See 3 more Smart Citations
“…This interface, combined with the reduced stability of the SLN pentamer, may explain why an SLN monomer was found associated with the M3 site. As stated above, the residues involved are on the opposite face of the SLN transmembrane helix (Leu 8 , Phe 12 , Leu 16 , and Ile 20 ) compared to the residues that stabilize the model of the SLN pentamer (Leu 10 , Ile 14 , Ile 17 , Leu 21 , Leu 24 , and Ser 28 ), and the SLN monomer appears to form a more direct interface with M3 of SERCA than the PLN pentamer. The different interactions between PLN and SLN and the M3 site of SERCA correlate with distinct functional effects on the V max of SERCA.…”
Section: Interaction Between Serca and Slnmentioning
confidence: 88%
“…1). The SLN residues involved include Leu 10 , Ile 14 , Ile 17 , Leu 21 , Leu 24 , and Ser 28 , and they compare favorably with the PLN resides implicated in pentamer formation (Ile 33 , Leu 37 , Ile 40 , Leu 44 , Ile 47 , and Leu 51 ). However, the SLN residues formed complementary interfaces that separately stabilized an SLN dimer and trimer (Fig.…”
Section: Molecular Model Of the Serca-sln Complexmentioning
confidence: 95%
See 2 more Smart Citations
“…4 SLN plays a key role in Ca 2+ homeostasis of muscle cells by inhibiting SERCA, and also participates in metabolism by inducing unproductive ATPase activity of SERCA and stimulating non-shivering thermogenesis. 5 SLN consists of three functional domains: (i) an unstructured N-terminus (NT, residues M1-E7) that contains a site for phosphorylation by the calmodulindependent protein kinase II (CaMKII) at residue T5; 6 (ii) a transmembrane helix (TM, residues L8-V26) that is important for SERCA binding as well as for selfassociation; 7,8 and (iii) a conserved luminal C-terminal domain (CT, residues R27-Y31) that protrudes into the SR lumen (Figure 1). 9,10 Experiments and molecular simulation studies have shown that the NT domain plays a primary role in SERCA uncoupling, while the TM domain is necessary for binding and stabilizing the regulatory complex as well as for inhibiting Ca 2+ affinity.…”
Section: Introductionmentioning
confidence: 99%